The Use of Pictionary Game in Teaching Vocabulary to Second Grade Students of SMPN 1 Raya - Uni Wanni Purba; Kammer Sipayung; Febrika Lumbantoruan; Renata Vonbora Simanjuntak (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2022)
Pictionary game is a fun and enjoyable guessing word game that can motivate students to learn English. This research deals with improving students’ vocabulary by using the Pictionary game for the second-grade students in SMP N 1 Raya. This research aims to determine whether the Pictionary game can increase students’ vocabulary. This study applied Classroom Action Research (CAR). The sample of the research was the second-grade students of SMP N 1 Raya in academic 2021/2022. The writer used two cycles that occur of two meetings. The finding of this study was that the Pictionary game can improve students’ vocabulary. It can be proved from the calculation of the test in both cycles. In the pre-test, the mean of the students’ score was 62,18. In post-test cycle I, the mean of vocabulary score was 72,84 and the mean score in post-test cycle II was 77,09. Based on the data, it could be concluded that there was a significant improvement in students’ vocabulary by using the Pictionary game. Based on the research, it is suggested that English teachers should use the Pictionary game as a technique in teaching vocabulary.